Portable C/C++ code for portable XML data - Zhaoqing Wang; Cheng, H.H. (IEEE software, 2006)
Ch XML packages integrate an embeddable C-compatible interpreter with XML C/C++ toolkits giving developers the option of using portable C/C++ scripts to process portable XML data. XML is changing the world of information sharing and exchange by letting users clearly define their data and documents for specific tasks, such as electronic data interchange, content management, or publishing. XML uses context encapsulation to separate content from presentation and to support a hierarchical structure among data from various sources. XML data is reusable, easily derivable, and reconfigurable. However, XML-based applications need a programming technology to perform processing-related tasks such as parsing, generating, manipulating, and validating the data. Application developers commonly use toolkits based on C/C++, such as Gnome's XML C parser and toolkit, Oracle's XML developer's Kit for C/C++ (XDK), and Microsoft's XML parser. These toolkits reflect the rich set of facilities, data types, operators, control structures, and runtime library functions that make C/C++ such a popular programming language. In fact, these tools, as well as the large number of skilled C/C++ programmers, often make C/C++ the preferred language for building portable systems